(untitled) - Brussee, Warren (New York , N.Y., 2006)
All About Six Sigma provides clear, straightforward explanations of how to apply Six Sigma so no matter what your experience, you can introduce, implement, and complete a Six Sigma project. Warren Brussee presents a simplified form of the most common Six Sigma tools, providing techniques for easy application while optimizing processes and results.
Keywords: Six sigma ( Quality control standard ),Total quality management